Martin Luther and Contemplation - Dubbelman, Samuel J. ca. 20./21. Jh.; Zoutendam, Erin Risch (2023)
This essay addresses the vexed topic of Martin Luther's relationship to late medieval mysticism through a terminological approach focused on Luther's use of the word contemplation. The contribution that this article offers arises from the often repeated observation that what is called mysticism today was called contemplation in the Middle Ages. To that end, this article seeks a clearer view of three things: 1) what Luther meant by contemplation, 2) whether his usage was continuous or discontinuous with medieval usage of the same term, and 3) the extent to which Luther's use of the term maps onto current scholarly discussions about ‘mysticism.’ Special attention is given to the first two, thereby laying the groundwork for further reflections by other scholars on the third.
Keywords: Martin Luther; Spirituality; Meditation; mystical theology; Mysticism; Contemplation